La resemantización del vanguardismo en Chirapu - Hurtado Lazo, Alex (2021)
The decentralism of the historical avant-garde in Peru allowed the emergence of intellectual voices in the regions that reflected on its cons-titution as a phenomenon in the cultural field. In the article, we will focus on the editorial proposal of Chirapu (Arequipa, 1928) through its intellectual nucleus, which carried out in its pages a resemantiza-tion of the avant-garde concept. Starting from the definition of internalperipheries as a place of enunciation, we will seek to understand the strategies that these intellectuals used to locate this movement in its “Indo-American” particularity; On the other hand, we will analyze the levels of resemantization in order to locate in their aesthetic and ideo-logical identification a legitimizing resource for the new Andean art.